Digital Transformation in Banking Sector: The Effect of Covid-19 Pandemic in Indonesia - Aisyah Nurjannah Siwi; Risna Triandhari; Raden Parianom (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The provision of digital services can support the need for integrated financial services, enhance operational cost efficiency, and improve financial performance. This research aims to examine the impact of providing digital services on the financial performance of banks before and during COVID-19, as well as to compare the impact on Islamic banks and conventional banks in Indonesia. This research utilizes secondary data from 15 Islamic banks and 20 conventional banks in Indonesia during the years 2017 - 2022, and estimates by static panel data model such as the fixed effect model (FEM) and random effect model (REM). The findings of this research indicate that the development of digital services significantly influences the financial performance of both Islamic and conventional banks, both before and during COVID-19. Furthermore, there are differences in the impact of providing digital services between Islamic banks and conventional banks before COVID-19. These findings may indicate the effectiveness of banks in developing services and enhancing overall technology adoption.